Innovation Performance of Family and Founder Firms: Empirical Evidence from German Listed Companies - Simon Mueller (Junior Management Science (JUMS), 2023)
Based on the agency perspective and the resource-based view of the firm, this study explores the impact of lone founder and family influence on innovation in-put and innovation output. By separating the lone founder and family effect into ownership, management, and governance influence dimensions, we analyze a pan-el data set of 165 German listed companies from 2013 through 2017. We first in-vestigate R&D intensity in lone founder and family firms versus other firms by using investments in research and development as a measure for innovation input. Secondly, we apply a negative binomial regression model to analyze R&D produc-tivity within the three types of firms by proxying innovation output with the filed number of granted patents within a certain year. According to the results, we mainly find that founder firms superiorly invest in innovation and strengthen their competitive position in the market through their entrepreneurial orientation. Family firms, on the other hand, might weaken future growth potential as they invest less in R&D and are not able to convert this lower input in superior innovation output.
Keywords: 650; Lone founder firms; Family firms; Innovation performance; R&D intensity; R&D productivity